Effects of 1α, 25‐Dihydroxyvitamin D3, the Natural Vitamin D Receptor Ligand, on the Pharmacokinetics of Cefdinir and Cefadroxil, Organic Anion Transporter Substrates, in Rat. Issue 11 (29th September 2014) - Kim, Yu Chul; Kim, In‐Bong; Noh, Chi‐Kyoung; Quach, Holly P.; Yoon, In‐Soo; Chow, Edwin C.Y.; Kim, Myungsoo; Jin, Hyo‐Eon; Cho, Kwan Hyung; Chung, Suk‐Jae; Pang, K. Sandy; Maeng, Han‐Joo
<x xml:space="preserve">Abstract</x> Evidence in the literature suggests that 1α, 25‐dihydroxyvitamin D3 [1, 25(OH)2D3], the vitamin D receptor ligand, down‐regulated the expression of the rat renal organic anion (renal organic anion transporter, rOAT) and oligopeptide (rPEPT) transporters, but increased intestinal rPEPT1 expression. We investigated, in rats, the intravenous and oral pharmacokinetics of 2 mg/kg cefdinir and cefadroxil, two cephalosporins that are eliminated via renal OAT1/OAT3 and are substrates of PEPT1/PEPT2, with and without 1, 25(OH)2D3 treatment. The area under the plasma concentration–time curve (AUC) of cefdinir or cefadroxil after 1, 25(OH)2D3 treatment was increased significantly because of decreased clearance (CL). Both kidney uptake and cumulative urinary recovery were significantly decreased, whereas liver uptake and fecal recovery remained unchanged in 1, 25(OH)2D3‐treated rats. Similar changes in AUC and CL were observed for both drugs upon coadministration of probenecid, the OAT inhibitor. Oral availability of cefdinir and cefadroxil remained unchanged with 1, 25(OH)2D3 treatment, suggesting lack of a role for intestinal rPEPT1. Rather, reduction of rOAT1/rOAT3 mRNA expression in kidney with 1, 25(OH)2D3‐treatment was observed, confirmed by decreased function in MDCKII cells overexpressing human OAT1 and OAT3. These composite results suggest that 1, 25(OH)2D3 treatment reduces cefdinir and cefadroxil clearances by diminution of renal OAT1/OAT3 expression, implicating a role for 1, 25(OH)2D3 in eliciting transporter‐based drug interactions. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:3793–3805, 2014